Environmental Footprint of the China-Pakistan Economic Corridor (CPEC): A Quantitative Approach to CO2 Emissions and Climate Effects - Sadia Shaikh; Muhammad Faisal Sultan; Imamuddin (Journal of Applied Research and Multidisciplinary Studies, 2024)
The current study is one of the initial and premier studies that was conducted to understand the environmental and climatic concerns related to China-Pakistan Economic Corridor (CPEC). The base of the theory was developed on pollution heaven hypothesis and analysis of selected variables was conducted through SMART-PLS via using Structural Equation Modeling (SEM). The analysis indicated that environmental concerns related to CPEC are not only perceived as the major predictors for CO2 emissions, however, they are also capable to harm climate and public health as well. The findings may help to develop a concrete policy framework for ongoing and upcoming phases of CPEC development. The framework would mitigate environmental risks associated with these activities and save the communities from environmental and health hazards of CO2 emissions. A substantial framework on this aspect would not only increase the economic and social significance of the project, however, it would also be a significant step towards addressing ecological and climatic harm to the environment. Hence, the current study is one of the pervasive studies that may not only increase the knowledge and research work associated with CPEC, however, it would also aid in policy formulation to further strengthen the Pak-China relationship.